Use of social media applications in classroom: analysis from education perspective. (April 2019) - Adnan, Muhammad; Giridharan, Beena
Abstract: The growing interest in research and technological advancement has opened doors of possibilities. Internet and virtual connectivity are such examples of possibilities. With its world wide web, the internet gave birth to social media that overthrew the old means of communication. Today, almost every field uses social media for various purposes. The field of education is no exception. Despite being popular for informal and entertainment use, social media is also used for a formal purpose like education. The current paper intends to review the use of social media in education. It presents the emergence of social media as a background that shall lead to its use in education. The paper reviewed three social media applications and their use in education in the light of previous studies. In doing so, some statistical data along with modes of use of social media in education have been discussed. It was found that social media applications like Twitter, Instagram and Facebook are helpful in achieving educational purposes. However, these benefits have been found to be surrounded by some drawbacks, a few of which the paper brought to light. Keeping in view the benefits and drawbacks of using social media in education, the paper proposed some recommendations. These recommendations revolve around promoting positive use of social media in education and mitigation of possible drawbacks. Finally, the paper draws a conclusion in the light of prior discussion and recommendations.